Experiences of mental healthcare providers regarding integration of mental healthcare into primary healthcare at the iLembe health district in KwaZulu-Natal province - Siphiwe T. Madlala; Respect M. Miya; Mdumiseni Zuma (AOSIS, 2020)
Background: Institutionalisation of mental healthcare users was a prevalent treatment approach in the apartheid era in South Africa. The introduction of community-based mental healthcare is aimed at improving mental healthcare services. The integration into primary healthcare improves access to mental health services. This integration is implemented by professional nurses working in the primary healthcare clinics. Aim: The aim of this study was to explore and describe experiences of professional nurses regarding integration of mental health into primary healthcare at the iLembe district of KwaZulu-Natal. Setting: This study was conducted at a public hospital in the iLembe health district of KwaZulu-Natal province. Methods: An explorative, descriptive and contextual qualitative research study was conducted. Semi-structured interviews were conducted with 15 professional nurses. Data were transcribed verbatim, organised into codes and finally analysed thematically using Tesch's method of data analysis. Results: This study revealed that majority of participants experienced and faced challenges regarding integration of mental health into primary healthcare. Professional nurses stated that they require support from the management and training to equip themselves with knowledge and skills to render effective mental healthcare services. Conclusion: The integration of mental healthcare into primary healthcare is pivotal to ensure easy and accessible mental healthcare services to its users. This strategy requires planning and implementations of available policies and guidelines regarding mental healthcare. Furthermore, adequate funding is required to secure human and material resources to aid the integration of mental healthcare into primary healthcare.